Mengidentifikasi Minat Bakat Siswa Sejak Usia Dini di SD Adiwiyata - Indah Ayu Anggraini; Wahyuni Desti Utami; Salsa Bila Rahma (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
This paper is the result of a descriptive qualitative research that aims to find out about the interests and talents of students in elementary schools. The results of this study indicate that interests and talents refer to the results of students' understanding. The strategy applied by classroom teachers is to provide material interests and talents into learning materials, choose the right methods and media, remedial, build communication, set an example, give appreciation and knowledge, identify and choose assistance programs. Class teacher competence still needs to be improved so that students' interests and talents in learning can be better than before.